﻿The Effects of Intensive Early Stocking and Early Weaning on the Onset of Puberty and Reproductive Success in Beef Replacement Heifers - Chance Fiehler; John Jaeger; Justin Waggoner; Keith Harmoney; K.C. Olson (Kansas Agricultural Experiment Station Research Reports, 2022)
Management practices utilizing genetics, nutrition, and growth have commonly been studied to maximize the lifetime productivity of female beef cattle. However, heifers managed to have their first calf by 24 months of age have the greatest chance of achieving maximum lifetime productivity. One way for a heifer to calve by 24 months of age is to decrease the age at which she reaches puberty. Heifers reaching puberty 1 to 3 months before exposure to breeding maximized conception success, as was shown when heifers bred during their third estrus were 21% more likely to conceive than heifers that were bred during their first or second estrus. Also, heifers fed a high-energy diet during the post-weaning period displayed a decreased age at puberty and an increased pregnancy rate. Additionally, early-weaned heifers fed a high-energy diet at an early age reached puberty at younger ages than those fed a low-energy control diet or those fed a high-energy diet beginning at six months of age. We hypothesized that heifers that were weaned at 120 days of age and provided a high-energy diet compared to the diet consumed by heifers weaned at a more conventional time of 205 days of age would display puberty at an earlier age and have improved first service conception and overall pregnancy rate.
Keywords: body condition score; estrus synchronization; first service conception; ultrasonography